Penerapan Hifdzul Bi’ah Dalam Fatwa Kupi Tentang Haramnya Kerusakan Lingkungan - Adhania, Putri Vidya (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2023)
Environmental damage is becoming an actual problem along with the increasing rate of population growth. The occurrence of environmental damage cannot be separated from human intervention. This is very contrary to the Al-Qur’an because Allah has prohibited humans from doing damage to the earth. This encouraged the initiators of environmental jurisprudence to add hifdzul bi'ah as a goal in maqashid syari'ah. This article will discuss the postulates and concept of hifdzul bi'ah in preserving the environment; history of the founding of KUPI; and how important hifdzul bi'ah is based on the KUPI fatwa regarding preserving the environment. This research is the result of a literature study using a descriptive-analytic approach. Currently, there is a lot of environmental damage caused by humans. The environment should be our collective responsibility. One of the initiators of environmental jurisprudence is KUPI. KUPI is a forum for Indonesian female ulama, who are concerned with contemporary issues using a gender perspective as one of their thinking methods. One of the KUPI fatwas is that it is haram to cause environmental damage. Hifdzul bi'ah becomes important if we are guided by the KUPI fatwa, for several reasons, namely: first, the environmental crisis is getting worse; second, Muslims need a comprehensive legal framework/guidelines regarding environmental issues; Third, classical jurisprudence does not accommodate environmental issues as a separate scientific discipline within the realm of Islamic studies. In formulating this fatwa, the KUPI team used the mubadalah (mutuality) method.